PERANCANGAN PERGERAKAN KAKI ROBOT HUMANOID MENGGUNAKAN SERVO DYNAMIXEL BERBASIS OPENCM 9.04 - Ulfa Wahyu Putri; Thamrin Thamrin (Universitas Negeri Padang, 2019)
The development of robotics technology in Indonesia has advanced very rapidly. It can be seen from the number of participants who took part in the Indonesian Robot Contest (KRI) that always increases every year. Organized by the Ministry of Research, Technology and Higher Education, this contest aims to accommodate students in the field of robotics so they can develop it and gain its benefits. One of the competitions at the Indonesian Robot Contest is KRSTI. Because of the writer’s interest in KRSTI, this research aims to make KRSTI robots that will dance with orders from music and robots that can perform foot movements while dancing Jaipong in which it is the theme of the KRI 2019 in division of KRSTI. On the foot movement, this humanoid robot has used the kinematic inverse calculation method with 3 DOF (Degrees of Freedom) which the movements are: the walkready, walk, right aslant walk, and left aslant walk. There are two software used in this humanoid robot namely OpenCM 9.04 robotic software, which is used to program humanoid foot robot programming, and Arduino nano software, which is used to program sound sensors that are input from the humanoid robots. When music is on, the sound sensor will receive serial data and sent it to Arduino nano, then Arduino nano will communicate the serial to the OpenCM 9.04 microcontroller and the robot will do movements according to the database or program that has been entered into OpenCM 9.04.Keywords: Humanoid Robot, KRSTI, OpenCM 9.04